Weed Management Strategies in the climate change era - Jinger, Dinesh; Dass, Anchal; Kumar, Vijaya; Kaur, Ramanjit; Kumari, Kavita (Indian Farming, 2018)
It is well established that both crops and weeds respond to climate change differently and weeds would be benefited to a great extent since these are naturally evolved with better adaptation capacities. The physiological plasticity of weeds and their greater intra-specific genetic variation compared with most crops could provide weeds with a competitive advantage in a changing climate scenario. Controlling and suppressing weeds would be more cumbersome and expensive under climate change. However, Resource Conservation Techniques (RCTs) and biological weed control could be important strategy for suppressing weeds. Prediction of future damage by weeds is very important for devising sustainable weed management.